Voice, (inter-)subjectivity, and real time recurrent interaction - Cummins, Fred (Frontiers in Psychology, 2014)
Received approaches to a unified phenomenon called "language" are firmly committed to a Cartesian view of distinct unobservable minds. Questioning this commitment leads us to recognize that the boundaries conventionally separating the linguistic from the non-linguistic can appear arbitrary, omitting much that is regularly present during vocal communication. The thesis is put forward that uttering, or voicing, is a much older phenomenon than the formal structures studied by the linguist, and that the voice has found elaborations and codifications in other domains too, such as in systems of ritual and rite. Voice, it is suggested, necessarily gives rise to a temporally bound subjectivity, whether it is in inner speech (Descartes' "cogito"), in conversation, or in the synchronized utterances of collective speech found in prayer, protest and sports arenas world wide. The notion of a fleeting subjective pole tied to dynamically entwined participants who exert reciprocal influence upon each other in real time provides an insightful way to understand notions of common ground, or socially shared cognition. It suggests that the remarkable capacity to construct a shared world that is so characteristic of Homo sapiens may be grounded in this ability to become dynamically entangled as seen, e.g., in the centrality of joint attention in human interaction. Empirical evidence of dynamic entanglement in joint speaking is found in behavioral and neuroimaging studies. A convergent theoretical vocabulary is now available in the concept of participatory sense-making, leading to the development of a rich scientific agenda liberated from a stifling metaphysics that obscures, rather than illuminates, the means by which we come to inhabit a shared world.